Horizontal inequity in the utilisation of healthcare services in Australia. Issue 11 (November 2020) - Pulok, Mohammad Habibullah; van Gool, Kees; Hall, Jane
Highlights: Inequity in the probability of any GP visit was slightly pro-rich in Australia. Inequity in the probability of specialist and dentist visits has remained pro-rich. The distribution of hospital-related care favouring the poor has become equitable. Policymakers should consider the potential impacts of policy reforms on equity. Abstract: The Australian universal healthcare system aims to ensure affordable and equitable use of healthcare services based on individual health needs. This paper presents empirical evidence on the extent of horizontal inequity (HI) in healthcare services (unequal utilisation by income for equal need) in Australia during the period of promoting reliance on private healthcare financing. Using data from the most recent Australian National Health Survey of 2011−12 and 2014−15, we examined and measured the extent of HI in eight indicators of out-of-hospital services and hospital-related care. Contrary to earlier studies, our results show a small but pro-rich inequity in the probability of general practitioner visits. Inequity in the distribution of specialist and dentist visits was in favour of richer people, a result that is commonly found in other developed countries and is also consistent with existing Australian evidence. Hospital-related care was equitably distributed compared to the pro-poor pattern found in earlier studies. Despite the universal health insurance system in Australia, there was inequity in the utilisation of needed healthcare services. Our evidence is relevant to similar health systems as governments move to higher out-of-pocket payments and other private sources to reduce pressure on public healthcare expenditure.